Functional significance of extent and timing of muscle activation during double poling on-snow with increasing speed - Zoppirolli, C.; Boccia, G.; Bortolan, L.; Schena, F.; Pellegrini, B. (European Journal of Applied Physiology, 2017)
Purpose: To evaluate the level of activation and timing of upper- and lower-body muscles during double poling at different speeds on snow. Methods: Nineteen well-trained cross-country skiers volunteered to double pole on a flat snowy track at different speeds (15, 18, 21 km/h). The target speeds could be maintained by the skiers thanks to the use of an audio-pace system in combination with cones spaced equally alongside the track. Only 11 subjects were finally included in the analysis, since their actual speeds, calculated through a photocell system, were within ±0.5 km/h from those requested. Cycle and poling durations were measured from the recordings of an accelerometer attached to a wrist, while the pattern and the level of muscle activation were evaluated from electromyographyc signals. Results: Double poling speed did not alter the sequence of muscle activation that started with hip flexors, continued with trunk flexors, shoulder, elbow and trunk extensors and ended with ankle plantar-flexors. However, higher speeds required an increasing involvement of thigh, trunk and shoulder muscles (P < 0.05) as well as an anticipation of their activation before pole plant (P < 0.05). Conclusions: A progressively earlier activation of trunk and lower limb muscles is a coordinative strategy that allows rapid achievement of optimal body posture prior to the exertion of poling phase. Moreover, earlier activation of these muscles as the speed increases provides adequate muscle stiffness in the shoulder and core regions for the acceptance of the poling load.